Growth and yield of crops and soil quality improvement in mango based agri-horticulture system - Sahu, Sarawati; Sah, R.B.; Kumar, Abhay; P.V., Dhanyashri (Indian Journal of Agroforestry, 2022)
A field experiment was carried out in Faculty of Forestry, Birsa Agricultural University, Ranchi, Jharkhand. To study the overall scenario of growth yield and soil properties under agri-horticulture system, to measure the changes under the influence of mango tree and intercrops grown in between. The experimental plots were laid out in randomized block design with two associate cropping systems (Mango + Mustard and Mango + Linseed), sole cropping (Mango, Mustard and Linseed each) with four replications. The growth parameters of mango viz. height, diameter, volume, crown height, crown length, crown width, crown area and yield of 3 2 mango were recorded 3.44 m, 12.14 cm, 0.04 m , 1.48 m, 1.95 m, 3.61 m 11.12 m and 36.68 kg/tree respectively were found significantly higher in mango+mustard followed by mango+linseed and minimum in sole mango. Yield attributes of mustard, plant height, no. of siliqua/plant, no. of seed/siliqua and 1000 seed weight and in linseed, plant height, no. of capsule/plant, no. of seed/capsule and 1000 seed weight, as well as yield of mustard and linseed were found significantly higher in sole cropping compared to mango based agri-horticulture system. The yield characters of mustard and linseed, such as grain yield (1072.25 and 897.00 kg/ha), straw yield (2031.75 and 1487.75 kg/ha) and biological yield (3104.00 and 2384.75 kg/ha) and harvest index (34.54 and 37.61 %) respectively were found significantly higher in sole cropping compared to mango based agri-horticulture system. Among soil physicochemical properties, pH, phosphorus, potassium, organic carbon and water holding capacity were at par in all the cropping systems